Establishing test and determination the normative levels to measure the block endurance of youth Volleyball Players - Mihaisin, A. Z. H.; Essa, D. H.; Essa, G. S. (Journal of Human Sport & Exercise, 2019)
The aim of this research establish levels of The volleyball player (youth) in test and defined levels of the players who took part in The Iraq champion ship of 2017 in the middle Euphrates Area in Iraq. To achieve the purpose of this study (50) players took part in this research, then the test is designed and two in block endurance skill are done sample from the original society. And the statistical treatment for variables of the(throw, stability and objectivity, the choice was put in the Final shape in which we can evaluate the Firmness of the repulsion wall so that the technical achieve mentis were divided into four levels (excellent, perfect, middle, low). Establishing test and defines standards off Volleyball block skill Endurance for youth player.